The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.mpdhp.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

An update on the molecular pathology of the intestinal polyposis syndromes

Abstract: The intestinal polyposis syndromes are characterised by multiple polyps of the large bowel, increased risk of colorectal cancer and a variety of extra-colonic manifestations. Most are caused by high-penetrance germline mutations in genes that affect signalling pathways (Wnt, BMP or mTOR) or the repair of base substitution mutations. However, there are exceptions to these rules: Lynch syndrome usually presents with few polyps; and hyperplastic (serrated) polyposis currently has no known genetic cause. Polyp mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Familial EC has been linked to germline mutations in the mismatch repair genes associated with Lynch Syndrome (LS), or to germline mutations in PTEN associated with Cowden Syndrome [5, 6]. A recent study has shown that germline missense mutations of POLE and POLD1 genes lead to development of polymerase proofreading-associated polyposis, which is similar to LS with regards to tumor spectrum, including an increased risk of ECs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Familial EC has been linked to germline mutations in the mismatch repair genes associated with Lynch Syndrome (LS), or to germline mutations in PTEN associated with Cowden Syndrome [5, 6]. A recent study has shown that germline missense mutations of POLE and POLD1 genes lead to development of polymerase proofreading-associated polyposis, which is similar to LS with regards to tumor spectrum, including an increased risk of ECs [7].…”
Section: Introductionmentioning
confidence: 99%